STEM- Based Multimedia Design for Stimulating HOTS in Theory Bioenergy and Wind Energy: Perception Physics Teacher - Farah Aulia; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2020)
The purpose of thiis research is to develop multimedia with the STEM approach to stimulate HOTS on bioenergy and wind energy materials. The research and development (R&D) method uses the ADDIE design which consists of 5 step, namely: analysis, design, development, implementation, and evaluation. This article will only report the first two stages namely analysis and design. The instrument used was a product needs analysis questionnaire and a practitioner validation sheet using a Likert scale. The data source of the needs analysis phase is high school students and physics teachers in Lampung Province. Product design validation was carried out by professional physics-teacher teachers with a Masters in Physics Education qualification. Where data is collected via Google Form and analyzed using descriptive qualitative. The results showed that multimeEdia to stimulate HOTS on bioenergy and wind energy was needed in the field. Multimedia which has the potential to stimulate HOTS on bioenergy and wind energy materials consists of videos and simulation of bioenergy and wind energy plants that contain all STEM.Keywords: bioenergy, multimedia, stimulating HOTS, STEM, wind energyDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202001